When to suspect hypogonadism in a patient with erectile dysfunction? - Knoblovits, Pablo (Revista del Hospital Italiano de Buenos Aires, 2022)
Hypogoandism should always be suspected in a patient with erectile sexual dysfunction and mainly when there is: decreased sexual fantasies, decreased libido and/or spontaneous erections and the diagnosis of a metabolic disorder (obesity, MS or type 2 diabetes mellitus). Older age is also a risk factor for low testosterone.